"A guiding light" : illuminating the path for French immersion teacher identity exploration - Aladin, Katija (2018)
This study aims to explore the phenomenon of teacher identity and more specifically second language teacher identity. The purpose of this research is to provide French immersion teachers in Alberta, Canada, a platform to share their stories and unique perspectives. This qualitative study was conducted in Alberta with in-service French immersion teachers. The data was collected by means of semi-structured interviews and the data was analysed using a dialogic narrative analysis approach. The narratives of each participant were/have been categorized into three sections: the social nature of identity, the discontinuity of identity and the multiplicity of identity. Each category offers a comparison of the similarities and differences between each participant that acknowledges the individuality of the teachers, as well as the French immersion community in which they belong. The enriching stories and perspectives provide insight into the challenging yet rewarding life of French immersion teachers. The findings from the study offer a tool and resource in French immersion decision making processes in the development of immersion programs as well as the necessity for teacher identity exploration.